Synthesis of Al2O3‐SiC powder from electroceramics waste and its application in low‐carbon MgO‐C refractories. Issue 3 (2nd November 2021) - Ma, Beiyue; Ren, Xinming; Gao, Zhi; Tian, Jialong; Jiang, Zhouhua; Zan, Wenyu; Yu, Jingkun; Qian, Fan; Cao, Yingnan; Fu, Gaofeng
Abstract: Composite additives are an efficient means to improve the high‐temperature stability and slag resistance of low‐carbon MgO‐C refractories. In this work, Al2 O3 ‐SiC powder was firstly synthesized from electroceramics waste by carbon embedded method at 1500°C, 1550°C, and 1600°C for 4 h, and then the as‐synthesized Al2 O3 ‐SiC powder was used as an additive to low‐carbon MgO‐C refractories. The effects of its addition amounts of 0, 2.5 wt.%, 5.0 wt.%, and 7.5 wt.% on the properties of the refractories were investigated in detail. It was found that increasing the heat treatment temperature is beneficial to the phase conversion of mullite and quartz to alumina and silicon carbide in the electroceramics waste. Furthermore, the addition of Al2 O3 ‐SiC powder effectively improves the performance of low‐carbon MgO‐C samples, and the formation of spinel dense layer and high‐viscosity isolation layer is the internal reason for the improvement of the oxidation resistance and slag resistance of low‐carbon MgO‐C samples. This work provides ideas for the reuse of electroceramics waste and presents an alternative strategy for the performance optimization of low‐carbon MgO‐C refractories.